Magnetic Resonance Angiography Using Fresh Blood Imaging in Oral and Maxillofacial Regions. (16th October 2012) - Oda, Masafumi; Tanaka, Tatsurou; Kito, Shinji; Habu, Manabu; Kodama, Masaaki; Kokuryo, Shinya; Miyamoto, Ikuya; Yoshiga, Daigo; Yamauchi, Kensuke; Nogami, Shinnosuke; Wakasugi-Sato, Nao; Matsumoto-Takeda, Shinobu; et al.
Abstract : The present paper provides general dentists with an introduction to the clinical applications and significance of magnetic resonance angiography (MRA) in the oral and maxillofacial regions. Specifically, the method and characteristics of MRA are first explained using the relevant MR sequences. Next, clinical applications to the oral and maxillofacial regions, such as identification of hemangiomas and surrounding vessels by MRA, are discussed. Moreover, the clinical significance of MRA for other regions is presented to elucidate future clinical applications of MRA in the oral and maxillofacial regions.